عزل وتشخيص بعض انواع البكتريا المرضية المسببة لألتهاب الأذن الوسطى في محافظة ذي قار: Isolation and identification of some bacteria that causes inflamation of otitis media in Thi-Qar - جفات نجلاء ناجي (University of Thi-Qar Journal of Science, 2013)
The current study included the isolation and identification of some bacteria that causes inflamation ofotitis media. Samples were collected from various patients in the consultative clinic of the AL-Habubi hospital in the governorate of Thi-Qar at the period from17/2-20/3/2012.The bacteria isolation was diagnosed depending on the properties of culture and using biochemical tests to show the ability of this bacteria of some producing some enzymes (positive or negative) Gram stain . The diagnosis 93 (53.14%) isolates of P. aeruginosa While number of isolates of Genus Staphylococcus was 67 (38.82 %) distributed as follows 55 (31.42%) isolates of Staphylococcus aureus and 12 (6.85%) isolates of Staphylococcus epidermidis .A s isolation of genus Streptococcus 15 (8.57%) acters bacteria Streptococcus pneumoniae. The results appeared highvarialabelty to antibiotic using , As bacteria P. aeruginosa showed high resistance for antibiotics ( Amoxcillen , Ampicillin ,Ceftazdime ) and lowest resistance for Cefotaxime is percentage of (13.89%) .As for S. aureus the high resistance was for antibiotics Rifampicin, Ampicillin, Trimethprim, Amoxcillen (100, 38.67, 34.45, 36.67) respectively while high sensitivity was for Cefotaxime in ratio (90.54%). As for S. pneumoniae high resistance was for antibiotic Amoxcillen in ratio(95.69%) while high sensitivity to Cefotaxime in ratio (90.78%) also resistant for antibiotics Ampicillin, Rifampicin , Trimethprim, Ceftazdime in ratio (28.97,30.86,37.46, 65.78%) respectively.